(untitled) (Research, Society and Development, 2021)
Objective: This study evaluated the bacterial removal in flattened root canals after preparation with different tapers of ProDesign Logic instruments. Methodology: Fifty-five mandibular incisors with flattened root canals were contaminated with a pure culture of Enterococcus faecalis ATCC 29212 for 21 days at 37ºC. Root canals preparation was performed using ProDesign Logic and 0.9% sterile saline solution for irrigation. The specimens were randomly allocated to three experimental groups (n = 15) according to the taper of the instrument used: 25.03, 25.04, or 25.06. Intracanal bacteriological samples were taken before (S1) and after (S2) preparation and the number of colony-forming units per milliliter (CFU/mL) was calculated. Differences in bacterial counts before and after treatment, within each group, were analyzed by the paired t-test. Groups were compared by ANOVA with a post hoc test. The level of significance was set at p <0.05. Results: Mature biofilm formation was confirmed at root canal walls by scanning electron microscopy. Bacterial colonies were significantly reduced in all experimental groups at S2 compared to S1 (p <0.001). No significant difference was observed between groups regarding the percentage of bacterial reduction (p >0.05). Conclusion: Preparation of flattened root canals using ProDesign Logic instruments with tapers of 0.03, 0.04 and 0.06 resulted in similar planktonic and bacterial biofilm reduction. None of the instruments rendered root canals completely free of bacteria.